2005
DOI: 10.1128/aac.49.7.3028-3030.2005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nebulized Liposomal Amphotericin B in Treatment of Experimental Pulmonary Aspergillosis

Abstract: The efficacy of therapeutic aerosolized amphotericin B (AMB) was studied in a steroid-immunosuppressed murine model of invasive pulmonary aspergillosis. Nebulized liposomal AMB can be a valid approach to the treatment of this infection, with subjects showing significantly improved survival relative to that of subjects given intravenous deoxycholate AMB, as well as lower lung weights and pulmonary glucosamine levels.Pulmonary disease is the most frequent form of invasive aspergillosis (4), a fungal infection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…In contrast, peak lung ITZ concentrations for aerosolized EPAS (25.9 g/g) and SFL (5.3 g/g) were substantially higher than concentrations achieved with SOL (1.5 g/g) and remained detectable for greater than 10 h following aerosolized administration of these formulations ( Table 1 (2,6,19). However, decreased in vitro activity and clinical failures with the use of amphotericin B have been reported for both A. flavus and A. terreus (1,9,15,22).…”
mentioning
confidence: 96%
“…In contrast, peak lung ITZ concentrations for aerosolized EPAS (25.9 g/g) and SFL (5.3 g/g) were substantially higher than concentrations achieved with SOL (1.5 g/g) and remained detectable for greater than 10 h following aerosolized administration of these formulations ( Table 1 (2,6,19). However, decreased in vitro activity and clinical failures with the use of amphotericin B have been reported for both A. flavus and A. terreus (1,9,15,22).…”
mentioning
confidence: 96%
“…Gavalda et al [76] studied the aptitude of remedial aerosolized amphotericin-B in a steroid-immune compromised murine model of attacking pulmonary aspergillosis. They compared a murine model of invasive pulmonary aspergillosis (IPA), for the competence of nebulized deoxycholate-amphotericin-B or liposomal AMB and then the banal intravenous (i.v.)…”
Section: Aerosolization Of Amphotericin-b (Amb)mentioning
confidence: 99%
“…For the treatment of IPA, they investigated the efficiency of nebulized AMB. Gavalda et al [76] concluded that for the cure of experimental disturbing IPA, AMB is a valuable method, with more apposite domino effect attained with nebulized-L amphotericin-B (NL-AMB) than with nebulized deoxycholate-amphotericin-B (ND-AMB). In the lungs, the suitable concentrations of both ND-AMB and NL-AMB were seen, though with liposomal formulation concentrations were perchance elevated.…”
Section: Aerosolization Of Amphotericin-b (Amb)mentioning
confidence: 99%
“…These can be either liquid, [8][9][10][11][12][13][14] solid, 14,15 or gaseous formulations. Over the years, liposomes have received widespread attention as a pulmonary drug delivery system, 8,16 providing an attractive means for noninvasive delivery and sustained release of drugs for treating chronic diseases, such as asthma and diabetes.…”
Section: Introductionmentioning
confidence: 99%